The new sectarianism: the Arab uprisings and the rebirth of the Shi'a-Sunni divide - Abdo, Geneive (Oxford University Press, 2016)
'The New Sectarianism' considers the causes for growing Sunni-Shi'a animosity in countries such as Iraq, Syria, Yemen, Iran, and Saudi Arabia. It illustrates how the two groups perceive one another after the Arab uprisings, how these perceptions have affected Arab life, and how these contestations pose a serious threat to the stability of regional states and stakeholders in the wider world.